Guerra em surdina : a ficção de Boris Schnaiderman entre a política e a poética - Assis, Ivone Gomes de (2014)
Hidden War: the fiction of Boris Schnaiderman between the political and poetic aims to present the political features of an era and Boris Schnaiderman´s poetics, through his prose, along 220 pages in 19 chapters of Hidden War, which narrates, in the literary event, the experience of war. Hidden War is a work of fiction that comprises a lot of memory snippets from its author, in The Second World War and in the geographic space of Brazil and Italy. The narrative, which begins in 1944, when some Brazilians were summoned to war, has its denouement in Italy and it is finalized with the regress of soldiers to Brazil after defeating Hitler in Germany. This dissertation is organized in 3 chapters, as follows: Boris Schnaiderman an officer of words, in which themes concerning the researched author will be addressed; 2. Literature and War; 3. From wreckage to History, the fiction used to analyze the researched literary work. The pre and post textual context are included; and the post textual aspects are the conclusion and references. Boris Schnaiderman is one of the most cited and well-known translators of Russian in Brazil however his work is still underexplored in the academic universe, especially in the field of Literature. The researches that I found on my research, which refer this work, Hidden War, are, mostly, related to the field of History, and none of them is exclusively about this work itself, fact that does not make it impossible that some of his other work may have not been reached.